Enhanced nitrogen use efficiency, growth and yield of wheat through soil urea hydrolysis inhibition by Vachellia nilotica extract - Rana, Muhammad Ajmal; Mahmood, Rashid; Nadeem, Faisal; Wang, Yun; Jin, Chongwei; Liu, Xingxing (Frontiers in Plant Science, 2022)
Soil urease inhibition slows down the urea hydrolysis and prolongs nitrogen (N) stay in soil, resulting in an increased N uptake by plants. Apart from several chemical urease inhibitors, the urease inhibition potential of plant extracts is rarely reported. In our previous study, the soil urease inhibition by Vachellia nilotica leaf extract was reported; however, its role in relation to growth and yield of wheat (Triticum aestivum) under pot and field conditions remains unknown. The acetonic extracts of 10, 20, and 50 g Vachellia nilotica leaves were given code names viz. Vn.Fl-10, Vn.Fl-20 and Vn.Fl-50, respectively, and coated on 100 g of urea individually. The enhancements of growth (total number of tillers, number of productive tillers, number of spikelets per spike, number of grains per spike, and 1000-grains weight) and yield (biological yield, straw yield, and grain yield) parameters of wheat by Vn.Fl-20 and Vn.Fl-50 coated urea treatments were compared with uncoated urea in a pot experiment. The experiment indicated that the Vachellia nilotica extract coatings were effective at improving N persistence in soil, as reflected by increased grain and straw N concentrations as well as uptakes. The reproduction of the aforementioned results, at the half and full recommended dose of urea under field conditions, reconfirmed the effectiveness of Vachellia nillotica coatings. Moreover, the Vn.Fl-20 and Vn.Fl-50 coated urea, at the half as well as full recommended dose under field conditions, proved equally effective in terms of higher biological, straw, and grain yield, and grain N uptake. The increments in the total number of tillers, number of productive tillers, 1000-grain weight, biological yield, straw yield, grain yield, grain N concentration, grain N-, and straw N uptake along with nitrogen use efficiency (NUE) components, i.e. nitrogen partial factor productivity (NPFP), nitrogen agronomic efficiency (NAE), partial nitrogen balance (PNB), and nitrogen recovery efficiency (NRE) of wheat highlighted the superiority of Vn.Fl-20 coating over the hydroquinone (Hq) coating on urea at the full recommended dose under field conditions. Given the findings of this study, Vachellia nilotica leaf extract coating (Vn.Fl-20) can be used as a natural urease inhibitor to reduce urea hydrolysis and enhance wheat productivity.